Psychological and Pedagogical Conditions for the Formation of Digital Literacy of Secondary School Students in the Conditions of “Education 5.0” - Balgabayeva, A.; Kitibayeva, A.; Karimova, G.; Aitzhanova, R.; Sultanbek, M. (Forum for Linguistic Studies, 2025)
In the context of the digital transformation of society and global educational reforms, the problem of developing digital literacy among secondary school students is of particular importance. This study is aimed at identifying psychological and pedagogical conditions conducive to the development of digital skills of Kazakh-speaking students. The research is based on a theoretical analysis of existing approaches to digital literacy and empirical data obtained through surveys and interviews with teachers and students. The identified factors include pedagogical support, the use of interactive and digital teaching methods, access to modern digital resources and technologies. The results of the study show that the successful development of digital literacy is associated not only with the technical support of the educational process, but also with psychological and pedagogical conditions, such as creating favorable conditions for digital learning and increasing the digital competence of teachers. In particular, innovative methods based on the concept of Education 5.0 are aimed at personalizing learning, using artificial intelligence and integrating digital technologies into educational programs. The practical significance of the work lies in the development of proposals for the effective implementation of digital technologies in educational processes that contribute to the development of digital literacy and the readiness of students to meet the challenges of modern society.
Keywords: Digital Literacy; Psychological and Pedagogical Conditions; Secondary Schools; Education 5.0; Digital Education